Prevalance of Noise Induced Hearing Loss among Traffic Police Personnel of Kathmandu Metropolitan City - Shrestha, I; Shrestha, B L; Pokharel, M; Amatya, R C M; Karki, D R (Kathmandu University Medical Journal, 2012)
Background Noise induced hearing loss (NIHL) is a major preventable occupational health hazard. Objective To measure permanent threshold shift in traffic police personnel due to noise exposure and to examine whether it was associated with duration of noise exposure, years of work and risk factors. Methods Cross sectional, descriptive study conducted at Dhulikhel hospital, Kathmandu University Hospital in 110 responding traffic police personnel. Detailed history and clinical examination of ear, impedence audiometry and pure tone audiometry was performed. Results Mean age group was 29.82 years; 82(74.5%) were males and 28 (25.5%) were females. Mean duration of service is 11.86 years. Twenty six (23.6%) had tinnitus and 39(35.5%) had blocked sensation in ear. Sixty five (59.1%) worked between 10-19 years. Alcohol and smoking shows positive impact on NIHL (p value =0.00). Odds ratio with 95% confidence interval were 4.481 (1.925-10.432) and 6.578 (2.306-18.764) respectively. Among 73(66.4%) noise induced hearing loss positive cases, bilateral involvement was seen in 45 (40.9%) and unilateral in 28(25.4 %) cases. Among unilateral cases most were left sided. Hearing threshold at 4 kHz increased according to age and duration of service. Conclusion Traffic police personnel are in constant risk of noise induced hearing loss. Screening for hearing loss is recommended for people exposed to noise. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6343 Kathmandu Univ Med J 2011;9(4):274-8